PHOSPHORUS AND NANOPHOSPHORUS IN MEDICINE AND BIOLOGY - Shtokaluk, K.V.; Gorchakova, N.A.; Zaichenko, A. V.; Chekman, I.S. (The Ukrainian Scientific Medical Youth Journal, 2017)
Phosphorus plays the important role in metabolic processes comes in composition of nucleic acids, macroergic compounds, phosphorus is contained in the bone tissue, less in the brain tissue, muscles, blood. Phosphorus is in the structure of drugs. Thanks to the nanotechnology, phosphorus is received as the nanophosphorus particles that is able for agglomeration, have a paramagnetic sensitivity. Nanophosphorus is used for the means’ creation on visualization, many-sided nanoprobes and drugs transporters. Phosphorus is in the phosphides’ structure, combination with the metals that is used in tomography.